The Origin of Primary Plastids: A Pas de Deux or a Ménage à Trois? - Baum, David (American Society of Plant Biologists, 2013)
The idea of an endosymbiotic origin of plastids has become incontrovertible, but many important aspects of plastid origins remain obscured in the mists of more than a billion years of evolutionary history. This commentary provides a critical summary of a recent proposal that primary plastid endosymbiosis was facilitated by the secretion into the host cytosol of effector proteins from intracellular Chlamydiales pathogens that allowed the host to utilize carbohydrates exported from the incipient plastid. Although not without flaws, the model provides an explanation for why primary plastids have evolved so rarely and why Archaeplastida, among all phagotrophic eukaryotes, succeeded in establishing primary plastids.